Intensification of flow blending technology in the production of motor fuels by the method of mathematical modelling; Chemical Engineering and Processing: Process Intensification; Vol. 122 - Ivanchina E. D. Emilia Dmitrievna; Dolganov I. M. Igor Mikhailovich; Chuzlov V. A. Vyacheslav Alekseevich; Belinskaya N. S. Natalia Sergeevna (2017, 2017)
Title screen